The experiences of young people, parents and professionals of using the attend anywhere video consultation system in a child and adolescent mental health service: a mixed-methods approach - Gormley, Emer; Melia, Ruth; McCormack, Sharon; Paige Phayer, Bonita; Madden, Jessica (Frontiers in Child and Adolescent Psychiatry, 2023)
In 2020, Attend Anywhere video consultation service was introduced across the Irish public health service to facilitate the provision of health interventions remotely in light of Covid 19related restrictions. This study aims to explore the experiences of young people, their parents and their clinicians, of using the newly introduced Attend Anywhere video consultation as part of their Child and Adolescent Mental Health Service (CAMHS).Method: A cross-section of twenty-nine young people, their parents and clinicians working in CAMHS Clare completed a survey pertaining to their experiences of using Attend Anywhere as part of their service. A cross-disciplinary research steering group of CAMHS clinicians adapted the NHS Scotland evaluation of Attend Anywhere / Near Me survey to better capture experiences in a CAMHS setting. The survey included both quantitative and qualitative items. Descriptive statistics were used to examine quantitative data. Qualitative data was analysed using Thematic Analysis.Results/Findings: Results demonstrated a decrease in the number of barriers reported by clients and professionals in accessing the CAMH service following the introduction of Attend Anywhere video consultation. Overall, the majority of professionals reported that they would use Attend Anywhere again, whereas almost a quarter of clients reported that they did not wish to use it again. Clients indicated a preference for receiving face-to-face services over other service provision options and this finding was associated with not having to rely on technology or manage connectivity issues and finding it easier to build the therapeutic relationship in-person.Findings suggest that both professionals and clients value face-to-face service provision while also acknowledging the benefits of Video Enabled Care in overcoming access barriers. We conclude that VEC be offered as an option in a blended service model, in conjunction with rather than as a replacement of face-to-face service provision.